1998
DOI: 10.1046/j.1365-2109.1998.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin C and astaxanthin on stress and disease resistance of postlarval tiger shrimp,Penaeus monodon(Fabricius)

Abstract: Postlarvae of tiger shrimp, Penaeus monodon (Fabricius), were fed semipurified diets supplemented with various levels of astaxanthin (AX) and ascorbic acid-polyphosphate (ApP): three groups were fed 230 mg AX kg -1 diet combined with 100, 1700 and 3400 mg ascorbic acid (AA) kg -1 diet, respectively; two diets contained 810 mg AX kg -1 mixed with 200 and 1700 mg AA kg -1 , respectively. Each treatment was run in four replicates. Incorporated levels of AA and AX, production output, and physiological condition we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 14 publications
(17 reference statements)
5
27
0
Order By: Relevance
“…1992). However, we did demonstrate that increasing phyllosoma AA concentrations had a moderating effect on stress indices, implying improved stress resistance, comparable to results found in other fish and crustaceans (Merchie et al . 1998; Kolkovski et al .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1992). However, we did demonstrate that increasing phyllosoma AA concentrations had a moderating effect on stress indices, implying improved stress resistance, comparable to results found in other fish and crustaceans (Merchie et al . 1998; Kolkovski et al .…”
Section: Discussionsupporting
confidence: 90%
“…In a number of crustacean and fish species, improvements to the normal patterns of growth, survival and stress resistance have been attained with high doses of AA delivered via AP enriched live feeds (Liu et al . 1989; Merchie et al . 1993, 1998; Kolkovski et al .…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of resistance in penaeid shrimp postlarvae to oxygen depletion stress (Chien et al 1999), salinity stress (Darachai et al 1998; Merchie et al 1998; Chien et al 2003), thermal stress (Chien et al 2003), ammonia stress (Pan et al 2003) and again, oxygen depletion in our study, was found to be associated with an increase in dietary astaxanthin. Shrimp fed the diets containing 400 and 200 mg astaxanthin/kg diet showed no significant differences in survival during the 9‐d stress test.…”
Section: Discussionsupporting
confidence: 65%
“…); likewise, administration of up to 810 mg astaxanthin kg −1 diet for 4 weeks had no effects on the postlarvae of giant tiger prawn P. monodon (Merchie et al . ). These results agree with the observations in giant freshwater prawn M. rosenbergii (Angeles et al .…”
Section: Safety Of Astaxanthinmentioning
confidence: 97%